PROFESSIONALISM AND PERFORMANCE OF COUNSELOR AT SMP NEGERI KOTA METRO - Noor, Marzuki (Universitas Muhammadiyah Metro, 2013)
Abstract: Teachers are professional educators with the primary task of educating, teaching, guiding, familiarize, train, assess, and evaluate students in Early Childhood Education, formal education, primary education and secondary education. Teachers addition must have adequate educational qualifications, basic capabilities, competence, must also have a sense of responsibility. Guidance counseling is one of the functions of guidance services in schools in addition to the function of administrative services and service learning or teaching. Professionalism has an idea of a person who pursue jobs based on skills, abilities, techniques, and procedures based on intellectual. Conceptually performance of teachers includes three aspects, namely, (1) professional ability, (2) social skills, (3) the ability of personal (private). Academic Qualifications: Academic qualification is the minimum educational level must be evidenced by a diploma or certificate of membership to the relevant statutory provisions in force. Factors affecting performance among the counselors is a factor Qualifications Education, teacher competence and responsibility implementation of the tasks of the profession. These three factors have to be studied so that the performance of counselors in running the service function will be seen from how to discipline, ability to work, and work performance counselor.Keyword: Professionalism, Performance, Counselor.